Contribuição dos receptores b1 e b2 de cininas em músculos liso vascular e não-vascular pelo rompimento seletivo dos genes que codificam os dois receptores: reavaliação dos efeitos farmacológicos da bradicinia e das interações cruzadas com angiotensina ii e endotelina-1 - Felipe, Sandra Arantes [UNIFESP] (2009)
Purpose: to pharmacologically characterize the responses to bradykinin (BK) and other agonists in non-vascular (stomach fundus) and vascular (aorta) smooth muscles isolated from kinin B1 and B2 receptor knockout mice. Methods: stomach fundus and aorta were isolated from normal , B1 knockout and B2 knockout animals; isometric contraction recordings were obtained for potency and efficacy determinations of agonists; cumulatively and non-cumulatively increasing doses of agonists such as BK, desArg9BK (DABK), angiotensin II (AII) and endothelin (ET-1) were applyied. Results: Potency (pD2) values determined in stomach fundus of WT and KO animals revealed that the affinity of agonists was maintained. Concerning the maximal effect induced by agonists, the efficacy of BK, but not AII and ET-1 was reduced in KOB1 animals. In the vascular tissue, BK was shown to be less efficient in KOB1 and KOB2 than in WT. The responses to AII and to ET-1 were reduced in KOB1 animals but it was reverted in KOB2 animals. In addition, stomach from KOB1 was found to be impaired to relax to sodium nitroprusside whereas the relaxant response was inaltered in KOB2, indicating that the deletion of B1 receptor led to important changes in the Ca regulation mechanism. Conclusions: The finding that the relative affinity of the agonists was not affected in stomach from knockout animals suggested that in this tissue there is no cross talking between kinin receptors and other agonist receptors. However the reduction in the maximal response to BK1 receptor might favoured the homodimerization of B2, which lead to activation and dessensitization, inducing an accentuated tachyphylaxis to BK and also the reduced maximal effect. In the case of AII, which showed a high affinity and efficacy, but the tachyphylaxis was attenuated in knockout animals, it can be suggested that there was formation of homodimers of B2 receptors rather than heterodimers between kinin B2 and AII AT1 receptors due to the absence of B1 receptors. Concerning BK- but not DABK induced effect in abdominal aorta in normal and knockout animals, indicated that B1 receptors would not express in this tissue. But the drastic reduction in change in sensitivity of the aorta towards BK-induced contraction suggested that B1 receptor should be mediating kinin mediated effect. The finding that the efficacy of ET-1 was reduced in KOB1 whereas that of AII was affected in aorta of the two knockout animals suggest that there must be cross talk between kinin receptors and of ET-1 and AII or between signal transduction activateed by these agonists. It is concluded that B1 and B2 receptors in stomach fundus and in abdominal aorta both receptors play important role for functional expression of kinins and that they are involved in the mechanisms of cell signaling, affecting the vascular and non-vascular smooth muscle contraction and relaxation.